2015
DOI: 10.1128/jb.00433-15
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Mycolic Acid Biosynthesis Genes and Their Regulation during Starvation in Mycobacterium tuberculosis

Abstract: Mycobacterium tuberculosis, the etiological agent of tuberculosis, is a Gram-positive bacterium with a unique cell envelope composed of an essential outer membrane. Mycolic acids, which are very-long-chain (up to C 100 ) fatty acids, are the major components of this mycomembrane. The enzymatic pathways involved in the biosynthesis and transport of mycolates are fairly well documented and are the targets of the major antituberculous drugs. In contrast, only fragmented information is available on the expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 77 publications
3
24
0
Order By: Relevance
“…A recent study found that genes involved in mycolic acid biosynthesis, modification and transport are regulated upon starvation in M. tuberculosis. Among these, M. tuberculosis fbpA and fpbB were down-regulated upon starvation (29). Consistent with these studies, fbpA and fbpB were also found to be downregulated upon extended intracellular persistence of M. tuberculosis into macrophages, an environment where nutrients availability become rapidly limiting (30).…”
Section: Regulation Of Gene Expressionmentioning
confidence: 67%
“…A recent study found that genes involved in mycolic acid biosynthesis, modification and transport are regulated upon starvation in M. tuberculosis. Among these, M. tuberculosis fbpA and fpbB were down-regulated upon starvation (29). Consistent with these studies, fbpA and fbpB were also found to be downregulated upon extended intracellular persistence of M. tuberculosis into macrophages, an environment where nutrients availability become rapidly limiting (30).…”
Section: Regulation Of Gene Expressionmentioning
confidence: 67%
“…The three isoforms of the TMM-consuming Antigen 85 complex, encoded in M. tuberculosis by fbpA, fbpB and fbpC , have partially redundant acceptor specificities (Jackson et al, 1999; Puech et al, 2002). However only fbpC is upregulated in nutrient-starved M. tuberculosis (Betts et al, 2002; Jamet et al, 2015) making Ag85C an obvious candidate for performing synthetic reactions under that condition. Perhaps the more interesting question, however, is the source of the energetically-expensive TMM building blocks.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this cross-regulation might occur at a higher hierarchical level where a more global regulator might act in response to a generalized stress signal generated by the inhibition of MA biosynthesis, turning down other enzymes related to this metabolism. In relation to these results, it has been recently demonstrated that starvation of M. tuberculosis also leads to a generalized downregulation of genes required for the synthesis (this include fasII , mabA-inhA and hadABC operon genes), modification and transport of mycolates [ 49 ]. As this is a highly energy-consuming process, it is physiologically relevant for the cell to slow down its synthesis during nutrient scarcity.…”
Section: Discussionmentioning
confidence: 99%